Pengujian Aplikasi Sistem Informasi Akademik Berbasis Website Menggunakan Teknik Equivalence Partitioning dan Metode Black Box - Yulianti Yulianti; Teti Desyani; Redo Ramadhan Chaniago; Hadi Iswanto; Eko Suroso; Taufik Surya Hermanto (Jurnal Informatika Universitas Pamulang, 2022)
This academic information system still has shortcomings in the data validation process, which will cause the data stored in the database not to match the desired data. Then it is proposed to test using the Black Box method with Equivalence Partitioning Techniques as a whole regarding the use, benefits, and results obtained from using the software. Black-box testing is a very important testing technique because it can identify errors in functions, interfaces, sample data, and access to external data sources. in implementation there are sometimes problems with testers who are not sure whether the software actually passes the test. in this implementation, the software that will be tested using black box testing is a website-based academic information system. Equivalence Partitioning Techniques discusses testing in the validation aspect of input data in terms of valid classes. From this research, it can be concluded that testing the level of accuracy of academic issues system software can provide the right solution for the school.